(untitled) (Scientia Agropecuaria, 2021)
Food development involves the usage of rapid sensory tools that allows for exploring consumer perceptions. The ideal sensory profile of cabanossi with llama meat from three feeding systems (with natural hay, alfalfa and with vitamins) through the CATA method was determined in comparison with two commercial samples. Moisture, pH, water activity, color and texture were evaluated. Moisture and external and internal color were similar between llama cabanossi but different from commercial ones. The mechanical parameters (hardness and chewiness) were superior from the llama cabanossi samples. Eighty (80) consumers with an ideal profile based on CATA questions found significant differences in all of the used descriptors. The indispensable sensory attributes for their acceptability were: salty, characteristic smell/ sausage and chewiness. With regards to the penalty analysis, the positive attributes (chewiness, and bland/soft) and negative (hard, smell, smokey and brown color), which should be considered for product reformulation. The cabanossi from natural hay feeding system (CS1) was close to the ideal product. The use of the ideal profile constitutes an alternative to identifying the characteristics (sensory, physicochemical and mechanical) for the development of new foods based on the consumer´s idealized requirements.